PENGARUH PEMBERDAYAAN, KOMITMEN ORGANISASI DAN KOMPETENSI TERHADAP KINERJA PEGAWAI - Mujiarto Mujiarto; Ansir Ansir; Salma Saleh (Pascasarjana Universitas Halu Oleo, 2019)
The study is aimed to comprehend and explain: 1) The effect of empowerment on employees performance. 2) The effect of organizational commitment on employees performance. 3). The effect of competence on employees performance. 4) The effect of empowerment, organizational commitment, and competence on employees performance. The sample size in this study is 37 respondents who are the employees of Wakatobi Regency Fisheries and Marine Services (DKP). The sample was determined by using the census method. This type of quantitative research uses the multiple linear regression analysis tool. Multiple regression is performed on more than one independent variable. To help the processing of the data in this study, the researcher used SPSS for Windows. The result showed that empowerment has positive and significant effects on performance, this was proven by the value of tsig by 0.046. Organizational commitment has positive and significant effects on employee performance, this is proven by the value of tsig by 0,000. Furthermore, there is positive and significant effects between competence and employees performance variables, this is proven by the value of tsig by 0.000. In addition, the F test shows that empowerment, organizational commitment and competence have significant influence on employees performance with the significance level of 0,000 or 0%. So, the hypothesis proposed in the research can be approved.Keywords: empowerment, organizational commitment, competence, and employees performance.